Web Based Sales Information System for Crackers Products Using Laravel Framework - Muhammad Firosulhaq; Agus Athok Miftahuddin (NEWTON: Networking and Information Technology, 2026)
Home Industry Glagahan, which produces traditional kerupuk (crackers), faces several challenges in managing sales, stock recording, and product distribution, as these processes were previously carried out manually, leading to errors in record-keeping, loss of transaction data, and difficulties in generating structured sales reports. To address these issues, this study developed a Web-Based Sales Information System for Kerupuk Products using the Laravel framework supported by a modular e-commerce package, applying the Waterfall development method that includes requirements analysis, design, implementation, testing, and evaluation stages. The system provides features such as an online product catalog, automated transaction recording, integrated stock management, and sales reports based on specific periods, while system functionality was tested using the Black-box Testing method to ensure that it meets user requirements. The results show that the system successfully assists the business owner in managing sales and stock data more effectively compared to the previous manual method, although limitations remain, such as the lack of fully implemented online payment integration and a relatively simple user interface. In the future, this system can be further enhanced by integrating courier services, digital payment methods, and a more flexible user interface to support wider market expansion.